Impact of oral contraceptive use and menstrual phases on patellar tendon morphology, biochemical composition, and biomechanical properties in female athletes - Hansen, M.; Couppe, C.; Hansen, C. S. E.; Skovgaard, D.; Kovanen, V.; Larsen, J. O.; Aagaard, P.; Magnusson, S. P.; Kjaer, M. (Journal of Applied Physiology, 2013)
Sex differences exist with regards to ligament and tendon injuries. Lower collagen synthesis has been observed in exercising women vs. men, and in users of oral contraceptives (OC) vs. nonusers, but it is unknown if OC will influence tendon biomechanics of women undergoing regular training. Thirty female athletes (handball players, 18-30 yr) were recruited: 15 long-term users of OC (7.0 ± 0.6 yr) and 15 nonusers (>5 yr). Synchronized values of patellar tendon elongation (obtained by ultrasonography) and tendon force were sampled during ramped isometric knee extensor maximum voluntary contraction to estimate mechanical tendon properties. Furthermore, tendon cross-sectional area and length were measured from MRI images, and tendon biopsies were obtained for analysis of tendon fibril characteristics and collagen cross-linking. Overall, no difference in tendon biomechanical properties, tendon fibril characteristics, or collagen cross-linking was observed between the OC users and nonusers, or between the different phases of the menstrual cycle. In athletes, tendon cross-sectional area in the preferred jumping leg tended to be larger than that in the contralateral leg (P = 0.09), and a greater absolute (P = 0.01) and normalized tendon stiffness (P = 0.02), as well as a lower strain (P = 0.04), were observed in the jumping leg compared with the contralateral leg. The results indicate that long-term OC use or menstrual phases does not influence structure or mechanical properties of the patellar tendon in female team handball athletes.